First record of Tricholoma fulvocastaneum from Thailand - Rarunee Sanmee (2018)
Tricholoma fulvocastaneum is recorded from Thailand for the first time. This edible ectomycorrhizal fungus is associated with Castanopsis tribuloides (Fagaceae) in mixed evergreen forest in northern Thailand. Conventional and molecular methods were carried out to confirm its identity. © 2007 The Mycological Society of Japan and Springer-Verlag.